Results of a phase 1 trial combining ridaforolimus and MK-0752 in patients with advanced solid tumours. Issue 14 (September 2015) - Piha-Paul, S.A.; Munster, P.N.; Hollebecque, A.; Argilés, G.; Dajani, O.; Cheng, J.D.; Wang, R.; Swift, A.; Tosolini, A.; Gupta, S.
Abstract: Background: The phosphatidylinositol 3-kinase/protein kinase-B/mammalian target of rapamycin (PI3K-AKT-mTOR) signalling pathway is aberrantly activated in several cancers. Notch signalling maintains cell proliferation, growth and metabolism in part by driving the PI3K pathway. Combining the mTOR inhibitor ridaforolimus with the Notch inhibitor MK-0752 may increase blockade of the PI3K pathway. Methods: This phase I dose-escalation study (NCT01295632) aimed to define the dose-limiting toxicities (DLTs) and maximum tolerated dose (MTD) of combination oral ridaforolimus (rising doses starting at 20 mg, 5 days/week) and oral MK-0752 (1800 mg once weekly) in patients with solid tumours. No intrapatient dose escalation was permitted. Results: Twenty eight patients were treated on study. Ridaforolimus doses were escalated from 20 to 30 mg/day. Among 14 evaluable patients receiving ridaforolimus 20 mg, one DLT (grade 2 stomatitis, second episode) was reported. Among eight evaluable patients receiving ridaforolimus 30 mg, three DLTs were reported (one each grade 3 stomatitis, grade 3 diarrhoea, and grade 3 asthenia). The MTD was 20 mg daily ridaforolimus 5 days/week + 1800 mg weekly MK-0752. The most common drug-related adverse events included stomatitis, diarrhoea, decreased appetite, hyperglycaemia, thrombocytopenia, asthenia and rash. Two of 15 (13%) patients with head and neck squamous cell carcinoma (HNSCC) had responses: one with complete response and one with partial response. In addition, one patient experienced stable disease ⩾6 months. Conclusions: Combined ridaforolimus and MK-0752 showed activity in HNSCC. However, a high number of adverse events were reported at the MTD, which would require careful management during future clinical development.